Mechanism of Stimulation and Inhibition of Tonoplast H(+)-ATPase of Beta vulgaris by Chloride and Nitrate - Griffith, Christopher J. (1986)
The H(+)-ATPase of tonoplast vesicles isolated from red beet (Beta vulgaris L.) storage tissue was studied with respect to the kinetic effects of Cl(−) and NO(3)(−). N-Ethylmaleimide (NEM) was employed as a probe to investigate substrate binding and gross conformational changes of the enzyme. Chloride decreased the K(m) of the enzyme for ATP but caused relatively little alteration of the V(max). Nitrate increased K(m) only. Michaelis-Menten kinetics applied throughout with respect to ATP concentration. Nitrate yielded similar kinetics of inhibition in both the presence and absence of Cl(−). Other monovalent anions that specifically increased the K(m) of the ATPase for ATP were, in order of increasing K(i), SCN(−), ClO(4)(−), and ClO(3)(−). Sulfate, although inhibitory, manifested noncompetitive kinetics with respect to ATP concentration. ADP, like NO(3)(−), was a competitive inhibitor of the ATPase but ADP and NO(3)(−) did not interact cooperatively nor did either interfere with the inhibitory action of the other. It is concluded that NO(3)(−) does not show competitive kinetics because of its stereochemical similarity to the terminal phosphoryl group of ATP. NEM was an irreversible inhibitor of the tonoplast ATPase. Both Mg·ADP and Mg·ATP protected the enzyme from inactivation by NEM but Mg·ADP was the more potent of the two. Chloride and NO(3)(−) exerted little or no effect on the protective actions of Mg·ADP and Mg·ATP suggesting that neither Cl(−) nor NO(3)(−) are involved in substrate binding.